2012
DOI: 10.1002/anie.201200267
|View full text |Cite
|
Sign up to set email alerts
|

A Strong Bio‐Inspired Layered PNIPAM–Clay Nanocomposite Hydrogel

Abstract: The demand for robust hydrogels in pharmaceutical, biomedical, and industrial applications has motivated intense research efforts in these wet polymeric materials. [1] Recent advances have resulted in different strategies for creating highly stretchable polymeric hydrogels, including sliding-ring gels (SR gels), [2] nanocomposite gels (NC gels), [3] doublenetwork gels (DN gels), [4] macromolecular microsphere composite gels, [5] and tetra-poly(ethylene glycol) gels. [6] Among them, NC gels have attracted si… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
126
1
2

Year Published

2015
2015
2022
2022

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 209 publications
(133 citation statements)
references
References 59 publications
4
126
1
2
Order By: Relevance
“…Moreover, some research groups have developed nanocomposite hydrogels with ordered structures using techniques for assembling 2D nanosheets such as GO nanosheets, nanoclay, and some liquid-crystalline inorganic nanosheets. [133][134][135][136][137] These reported ordered structured nanocomposite hydrogels can serve as high-performance bioengineering materials for tissue engineering. Figure 7.…”
Section: Self-assemblymentioning
confidence: 96%
“…Moreover, some research groups have developed nanocomposite hydrogels with ordered structures using techniques for assembling 2D nanosheets such as GO nanosheets, nanoclay, and some liquid-crystalline inorganic nanosheets. [133][134][135][136][137] These reported ordered structured nanocomposite hydrogels can serve as high-performance bioengineering materials for tissue engineering. Figure 7.…”
Section: Self-assemblymentioning
confidence: 96%
“…When the content of Al was lower than that of GO (GO/AA = 6.5:3.5), the "pull-out" mode was the main toughening mechanism according to previous reports on binary artifi cial nacre. [ 45,51 ] With increasing Al content, the "pull-out" mechanism was partly weakened and the crack-defl ection mechanism was still not thoroughly formed, so that the failure strain decreased (ca. 3%).…”
Section: Communicationmentioning
confidence: 98%
“…hydrogels have been reported. These studies indicated that when such 2D CNPs are added to a polymeric hydrogel matrix, additional interactions take place between CNPs and polymers, resulting in the creation of nanocomposite hydrogels with improved mechanical properties, [33][34][35] stimuli-responsiveness, 36,37 swellability, 38 and self-healing abilities, 39 compared to hydrogels consisting of single hydrophilic polymers. This paper intends to review and analyze recent advances in clay mineral-containing nanocomposite hydrogels with an objective to highlight the state-of-the-art technologies used in the preparation of clay mineral-containing nanocomposite hydrogels.…”
Section: Jing Wangmentioning
confidence: 99%